The Interfacing Approach for Investigation Beyond Boundaries - Vita Fortunati (Universidade de Lisboa, 2013)
My essay will tackle with the following issues: 1 - The urgent need of integrated studies for understanding the complexity of our current culture environment We are aware that science and humanities are no longer two separate spheres of knowledge but two complementary and integrated ambits. Science has to take into accounts epistemological and ethical issues, humanities need to face and be aware of scientific developments and new conceptualisations. 2 - The concept of «interface» that has been the working hypothesis of the European project Acume2 Interfacing Science and Humanities. We have started by questioning the very idea of 'influence' (or 'mutual influences') in favour of a more dynamic idea of 'interfacing'. Therefore, a fundamental point of departure is to acknowledge the isomorphism of the two fields, recalling that they have often developed new models and strategies of investigation into complex scientific and cultural (artistic, literary) phenomena at the same time, simultaneously responding to their own actuality and societal matrices. 3 - I will present the methodology and the scientific results of two cases studies carried on by scientists and humanists on: Memory and on Bio-complexity.